Needle Stick Injury Report Application Design at XYZ Hospital in Tangerang - Setiawan, Haditya; Suryasari (ULTIMA InfoSys, 2025)
Needle stick injuries are a common occurrence among healthcare workers. There are potential risks of HBV, HCV, and HIV infection transmission to healthcare workers caused by needle stick injury accidents. At XYZ Hospital, reporting is done manually through paper-based forms that must be filled out and submitted to other departments. To expedite the process, the forms are photographed and sent via WhatsApp. Manual reporting is still considered inefficient, so a website-based reporting application was created that can be accessed quickly and easily via mobile phones, tablets, and laptops. To ensure the project meets requirements, the application was created using a prototype methodology, so it can be completed according to user needs. By implementing a website-based reporting application, it can simplify reporting, tracing, and more neatly documenting by reducing physical/paper documents and switching to digital documents.